2015
DOI: 10.1002/chem.201406058
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of Burkholderia Lipid A Modified with Glycosyl Phosphodiester‐Linked 4‐Amino‐4‐deoxy‐β‐L‐arabinose and Its Immunomodulatory Potential

Abstract: Modification of the Lipid A phosphates by positively charged appendages is a part of the survival strategy of numerous opportunistic Gram-negative bacteria. The phosphate groups of the cystic fibrosis adapted Burkholderia Lipid A are abundantly esterified by 4-amino-4-deoxy-β-l-arabinose (β-l-Ara4N), which imposes resistance to antibiotic treatment and contributes to bacterial virulence. To establish structural features accounting for the unique pro-inflammatory activity of Burkholderia LPS we have synthesised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 61 publications
3
30
0
Order By: Relevance
“…Here, we demonstrate a role for L-Ara4N residues in lipid A that explains why the B. cenocepacia LPS (naturally consisting of a mixture of penta-and tetra-acylated forms) acts as a strong TLR4⅐MD-2 agonist. Our results agree with a recent report by Hollaus et al (36) demonstrating that a synthetic Burkholderia lipid A substituted with L-Ara4N exclusively at the anomeric phosphate acts as a potent human TLR4⅐MD-2 agonist.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here, we demonstrate a role for L-Ara4N residues in lipid A that explains why the B. cenocepacia LPS (naturally consisting of a mixture of penta-and tetra-acylated forms) acts as a strong TLR4⅐MD-2 agonist. Our results agree with a recent report by Hollaus et al (36) demonstrating that a synthetic Burkholderia lipid A substituted with L-Ara4N exclusively at the anomeric phosphate acts as a potent human TLR4⅐MD-2 agonist.…”
Section: Discussionsupporting
confidence: 93%
“…The structural features of LPS BC suggest that the molecule would be a very poor TLR4⅐MD-2 complex agonist compared with the prototypic enterobacterial LPS. In contrast, several studies show that LPS BC as well as biological and synthetic lipid A analogues is highly proinflammatory (32)(33)(34)(35)(36). Therefore, the current model for binding/activation of human TLR4⅐MD-2 complex cannot explain why LPS BC is proinflammatory.…”
mentioning
confidence: 94%
“…Since the PivCl-mediated H-phosphonate coupling can be often accompanied by concomitant side-reactions (formation of P-acyl byproducts [ 140 ] resulting from an over-reaction of 96 or 98 with PivCl or formation of GlcNAc-derived oxazolines in the presence of an excess of chloroanhydride) [ 141 ], phosphonium type coupling reagents were optionally explored. Accordingly, the H-phosphonate 96 was activated by 3-nitro-1,2,4-triazol-1-yl-tris(pyrrolidin-1-yl)phosphonium hexafluorophosphate (PyNTP), which selectively reacted with the electrophilic phosphorus atom of the H-phosphonate to form a P–N activated intermediate [ 160 161 ]. The later was smoothly coupled to the nucleophilic component, the hemiacetal 82 .…”
Section: Reviewmentioning
confidence: 99%
“…Since the 1-phosphate group of lipid A is directly involved in the formation of the dimeric MD-2·TLR4-LPS complex [ 42 ], the appendage of β-L-Ara4N might enhance the efficiency of dimerization via ionic attraction. In order to elucidate the structural determinants responsible for the unique pro-inflammatory potential of Burkholderia lipid A, the pentaacylated Burkholderia lipid A esterified by β-L-Ara4N at the anomeric phosphate 101 and its Ara4N-free counterpart 102 corresponding to native Burkholderia LPS were chemically synthesised [ 161 ].…”
Section: Reviewmentioning
confidence: 99%
“…We have recently shown that application of the H-phosphonate approach is advantageous for such a purpose, compared to other phosphitylation methodologies. 14,15 Preparation of anomerically pure α- and β- H-phosphonate monoesters of orthogonally protected l -Ara4N in a stereoselective manner comprises a major synthetic challenge in the synthesis of Ara4N-containing phosphodiesters (Figure 2). …”
mentioning
confidence: 99%